2014
DOI: 10.5812/ircmj.7400
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Preeclampsia Prevention in Patients With Abnormal Uterine Artery Blood Flow

Abstract: Background: Preeclampsia is one of the leading causes of maternal mortality and morbidity. Its prevalence varies between 10-25% among high-risk pregnant patients. Objectives: The aim of this study was to determine whether treatment with acetylsalicylic acid (ASA) reduces the incidence of preeclampsia among pregnant women with abnormal uterine artery flow. Patients and Methods:In this double-blind, placebo controlled trial, 80 high-risk pregnant women with preeclampsia, who had abnormal findings on Doppler ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Obesity was present in 30 (18.8 %) having mean body mass index 25.23 ± 1.92 kg/m 2 which is quite close to that reported by Talari et al 18 has also reported that 17% patients developed preeclampsia before 32 weeks of gestation.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Obesity was present in 30 (18.8 %) having mean body mass index 25.23 ± 1.92 kg/m 2 which is quite close to that reported by Talari et al 18 has also reported that 17% patients developed preeclampsia before 32 weeks of gestation.…”
Section: Discussionsupporting
confidence: 82%
“…Ebrashy et al 16 has also reported 28.4 % previous history of pre-eclampsia while 20.4 % family history of preeclampsia; close to our results. Talari et al 18 has also reported similar results.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations